(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Cihateup duck is one of the local Indonesian poultry from West Java. These ducks are raised in Tasikmalaya and Garut. Cihateup duck has the potential to produce meat, but duck meat has been considered to have off-odor. components off-odor formed when the fatty acids are oxidized. A study with the aim to protect unsaturated fatty acids in local duck meat from oxidation using Pluchea indica Less (beluntas) and Cosmos caudatus (kenikir) in feed as the source of natural antioxidants. The study used was complete randomized design (RAL) with 7 treatments and 5 replications. The treatment was Pluchea indica Less or Cosmos caudatus powder with the duration of administration 1, 2 or 3 weeks before the age of harvest (10 weeks). Ducks used were 35 heads of Cihateup duck. Variables observed were moisture content, fat content, Malondialdehyde (MDA), composition of fatty acid, and sensory characteristic of duck meat. The results showed that the effect of Pluchea indica Less or Cosmos caudatus were not significant on moisture content and fat content. The effect of Pluchea indica Less or Cosmos caudatus on MDA, composition of fatty acid, and and off-odor intensities of duck meat during cooking was significantly different (P<0.05). It was concluded that this addition of Pluchea indica Less for 3 weeks or Cosmos caudatus for 2 weeks could lower off-odor on local duck meat.